1980
DOI: 10.1128/iai.28.1.17-23.1980
|View full text |Cite
|
Sign up to set email alerts
|

Antitoxic Cholera Immunity in Mice: Influence of Antigen Deposition on Antitoxin-Containing Cells and Protective Immunity in Different Parts of the Intestine

Abstract: The importance of the mode of antigen presentation (intravenous, oral, or enteral restricted to the lower ileum) in the development of a local immune response and immunological memory for such a response in different parts of the intestine was studied in mice. Cholera toxin was used as antigen and the immune response was assayed by determining both the number of specific antitoxin-containing cells in the lamina propria and protection against experimental cholera. The results showed that all of these routes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Lycke spleen after repeated intravenous immunizations (80% IgG) as opposed to that seen in lamina propria cells after oral immunizations (80% IgA) suggested that the sensitivity for detection of the different isotypes was high. The representation of the various isotypes in the lamina propria antitoxin response also closely resembled that previously reported for total Ig-containing cells using ACC technique [12]. Furthermore.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Lycke spleen after repeated intravenous immunizations (80% IgG) as opposed to that seen in lamina propria cells after oral immunizations (80% IgA) suggested that the sensitivity for detection of the different isotypes was high. The representation of the various isotypes in the lamina propria antitoxin response also closely resembled that previously reported for total Ig-containing cells using ACC technique [12]. Furthermore.…”
Section: Discussionsupporting
confidence: 85%
“…The sensitivity of this assay compared with other available techniques for detection of antigen-specific gut mucosal responses appears to be very high. The immunohistochemical detection of antibody-containing cells (ACC) in tissue sections or the measurement of specific antibodies in intestinal washings or in supernatants from cell cultures can only poorly detect antigenspecific responses after a single oral priming immunization with CT, whereas the method presented in this paper registered substantial primary antitoxin SFC responses in the lamina propria, especially when the sensitivity-enhancing vaseline border ring method was used [8,12,13,17]. Furthermore, the lower limit of sensitivity ofthe ACC technique has been reported to be around 100 ACC/mm\ with peak responses of 10,000-20.000 ACC/mm' to oral immunizations with CT [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olympus, Tokyojapan) in combination with a light microscope. The number of mast cells per mm" was calculated by Lange's method [14].…”
Section: Light Microscopic Observationmentioning
confidence: 99%
“…197 (1985) The Seeretory IgA Syndrom 331 secretory IgA antibodies protect against rhino-, myxo-and paramyxovirus infections (11). In experimental models it has also been clearly shown that secretory IgA antibodies can protect against cholera (27,30,32) and that this protection relates to the number of IgA-producing cells in the small intestine (30,32). In the human it has recently been demonstrated that secretory IgA in milk confers protection of the breastfed baby against Vibrio cholerae (18).…”
Section: Seeretory [Ga and Proteetion Against Infectious Diseasementioning
confidence: 99%